Unlocking the Trade Potential of the Palestinian Economy : Immediate Measures and a Long-Term Vision to Improve Palestinian Trade and Economic Outcomes - World Bank Group (World Bank, Washington, DC, 2017)
The Palestinian economy is severely hampered by trade-related restrictions, high logistics costs, cumbersome procedures and institutional inefficiencies. Operating within an uneven customs union arrangement with Israel, the Palestinian economy has accumulated an enormous trade deficit and overdependence on Israel’s economy and has neither could develop dynamic export-oriented sectors nor to tap into larger and more competitive third markets. Over the years, this situation has contributed to slow growth, high unemployment, and stubborn persistence of poverty in the Palestinian economy. A bold reform agenda is urgently required to improve the Palestinian economy’s trade outcomes. Immediate steps should be taken to reduce the burden of existing trade-related restrictions and transaction costs. The Palestinian economy should also begin the transition toward an autonomous trade regime, and can exercise control over its own customs territory, in line with its long-term economic interest. It should retain an open trade regime and develop its links with overseas markets. The economic relationship with Israel should be recast in a manner that is comprehensive and exploits the large synergies that exist between the two economies. Such a course will provide the Palestinian Authority with some of the tools and incentives to undertake far-reaching structural reforms. The reform agenda will neither be a simple endeavor nor will it alone determine the success or failure of the Palestinian economy. This note proposes ideas that could, in the fullness of time, and with the assistance of international donors help overcome existing dysfunctions and improve trade-related economic outcomes in the Palestinian economy.